An overview of counselling profession towards management in the practice - Lee, Ying Yin; Wan Jaafar, Wan Marzuki (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
This paper discuss about an overview about counseling, counseling process, counselor’s role and competencies, and ethics in counseling.